Os Hekhalot: Vestígios arqueológicos de um criptojudaísmo singular - Mendes, Pedro (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This paper presents a brief historic overview about Portuguese Crypto-Judaism it points out the reasons why finding and recognizing these archeological remains is dificult using the controversial hekhalot as an exemple, and identifies similarities and differences in the ambiguities and heterogeneities of these findings based on a summary table. Though this approach, the objective is to seek for a research model that can be applied to the study of other hekhalot using the case study of Oporto´s hekhal. A new possibly unknown hekhal located in Monforte (Portalegre) is then identified. Finally, the paper proposes an interpretation of the possible hekhalot in the context of Portuguese Crypto-Judaism.